Syllabus development workshop for master programme in accountancy / Siti Nabilah Mohd Shaari - Mohd Shaari, Siti Nabilah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Faculty of Accountancy, UiTM Perak Branch has moved one step ahead in proposing a Master Degree programme in Accounting and Information Technology (IT). Thus, a two-day workshop was conducted in February 2018 to develop a syllabus structured for the programme. This master programme will not only focus on the accounting area but Big Data Analytic will be given an emphasis too. This emphasis is in respond to the demand of Industrial Revolution 4.0 that university graduates must have the ability to cross fields and to be competent in multiple areas.